Effect of Tithonia Compost (Tithonia diversifolia) and Phosphorus On The Growth and Yield of Peanuts - Hutabarat, Rudi Saputra; Turmudi, Edhi; Setyowati, Nanik (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2019)
ABSTRACT This study aims to determine the effect of phosphorus dosage and tithonia compost on the growth and of peanut.The research had been conducted fromNovember 2017 to March 2018atBentiring Permai Village, Muara Bangkahulu Sub-District, Bengkulu City, Indonesiaat ± 10 m above sea level using Completely Randomized Block Design, two factors. The experiment was replicated three times. The first factor was tithonia compost with 2 treatment levels namely 0 ton ha-1 (control)and 20 ton ha-1. The second factor was dosage of phosphorus(SP-36)with 4 treatment levels, 25, 50, 75 and 100 kg ha-1.The results showed no interaction between compost and phosphorus dosage treatment on the growth and yield of peanut crops. Tithonia compost at 20 ton ha-1 increase the growth and yield of peanut crop. Application of tithonia compost paitanat 20 ton ha-1 resulted in higher increase plant height, crop dry weight, pod weightand yield of peanut53%, 58%, 67% and 71% respectively, compared to that of control plants (not compost). Phosphorus dosage had no significant effect on the growth and yield of peanut.Keywords: Peanut, Tithonia compost, Phosphorus